Maternal Oxidative Stress, Placental Morphometry, and Fetal Growth in Diabetic Rats Exposed to Cigarette Smoke - Sinzato, Yuri K. [UNESP]; Bevilacqua, Estela M.; Volpato, Gustavo T. [UNESP]; Hernandez-Pando, Rogelio E.; Rudge, Marilza V. C. [UNESP]; Damasceno, Débora Cristina [UNESP] (Springer Nature, 2018)
The diabetic syndrome affects pregnancy, contributing to placental functional and structural disruptions and impaired fetal development, with many reports indicating tobacco-associated morbidity and perinatal mortality. In our study, an experimental rat model of diabetes and cigarette smoke exposure in pregnant rats was used to determine the impact of the combination of diabetes and exposure to cigarette smoke during pregnancy on maternal oxidative stress biomarkers and placental and fetal development. Diabetes was induced by streptozotocin, and dams were exposed to cigarette smoke by mainstream smoke generated by a mechanical smoking device and delivered into a chamber. Four groups of dams were studied: nondiabetic (C, control) and diabetic (D) exposed to filtered air and nondiabetic (CS) and diabetic (DS) exposed to cigarette smoke prior to and during pregnancy. Maternal oxidative stress biomarkers, placental morphology, and fetal growth were determined close to term. The combination of diabetes and cigarette smoke resulted in elevated maternal blood glucose levels and increased number of small fetuses. Placentas from the DS group showed increased junctional zone and decreased labyrinthine area. The morphological alterations were characterized by extensive vascular congestion, thickness, and hyalinization of the vascular walls, numerous decidual cells with abundant glycogen, and macrophages with cytoplasmic inclusions of hemosiderin. Additionally, they showed increased glycogen accumulation and junctional zone structural derangement with ectopic giant cells. No alterations were observed in maternal oxidative stress status. Thus, our result suggests that diabetes makes pregnant rats more susceptible to the adverse effects of exposure to cigarette smoke on placental morphometry and fetal growth.
Keywords: cigarette smoke; diabetes; oxidative stress; placenta; pregnancy